Small Survey of Tractor or Power Tiller Owners in Benue State, Nigeria - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
Understanding the nature of farm tractors ownership and their uses by private individuals who are mostly in the informal sector, is critical in African countries like Nigeria. This survey captures relevant information from tractor owners in Benue state in Nigeria. Benue state was selected because it was one of the seven focal states selected by the USAID in which IFPRI Nigeria project was requested to conduct research in 2018. Among the 7 states, Benue state has been selected because IFPRI’s earlier work, as well as secondary survey data and interactions with the local stakeholders, suggested that there had been significant growths of private sector tractor ownership and hiring-out services, but they had remained largely in the informal sector and information had been lacking. The survey covers 71 tractor owners in Benue states. The survey captures information regarding the nature of tractor usages, hiring business operations, evolutionary histories, and what challenges they have been able to overcome or continue to face.